Concrete cracking and deflection analysis of RC beams strengthened with prestressed FRP reinforcements under external load action. (1st January 2021) - Slaitas, Justas; Valivonis, Juozas
Abstract: Fibre reinforced polymer (FRP) reinforcements (laminates, sheets, strips, rods) are considered for retrofitting of RC structures worldwide. Such reinforcements are light, easy to install, corrosion resistant, satisfying aesthetical and design requirements. In order to use full potential of the FRP it should be pretensioned, this way reducing crack widths and deflections. In most cases in practice strengthening will be carried out for structures exposed to external load with initial cracks and deflection. However, there is the lack of experimental and theoretical research of such phenomena when RC structure is strengthened with prestressed FRP reinforcements under external load action. Therefore, here will be presented experimental program for the full analysis of this phenomena. 14 identical RC beams were casted and tested at the courtesy of Vilnius Gediminas Technical University (VGTU): 2 control RC beams, 6 beams strengthened with prestressed carbon fibre reinforced polymer (CFRP) laminates without external load action, 6 beams – under external load action. Different prestressing levels were used in both cases: 17 ÷ 56% from the nominal load bearing capacity of FRP. Based on the results theoretical models for calculation are being presented for consideration.